2015
DOI: 10.13109/zptm.2015.61.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Personale Ressourcen in stationärer Fachpsychotherapie - Zusammenhänge und Entwicklung/ Personal resources in inpatient psychotherapy – Relationships and development

Abstract: Summary Personal resources in inpatient psychotherapy -Relationships and developmentObjective: We examined how personal resources develop during inpatient psychodynamic psychotherapy, their relationship to symptom development, Operationalized Psychodynamic Diagnosis (OPD-2), and sociodemographic aspects. Methods: 483 patients were examined using self-assessment questionnaires (Brief Symptom Inventory (BSI), Hospital Anxiety and Depression Scale (HADS), Inventory of Interpersonal Problems (IIP), Questionnaire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Moreover, social isolation is a prominent symptom in patients with depression (Matthews et al, 2016). Without specific interventions, social resources only increase with a small effect size over the course of inpatient treatment (Kati et al, 2015). Therefore, it is beneficial to strengthen social relationships with the help of specific interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, social isolation is a prominent symptom in patients with depression (Matthews et al, 2016). Without specific interventions, social resources only increase with a small effect size over the course of inpatient treatment (Kati et al, 2015). Therefore, it is beneficial to strengthen social relationships with the help of specific interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that resource realization correlated with an improvement of symptoms during inpatient treatment and with a shorter duration of psychotherapy (Flückiger & Grosse Holtforth, 2008; Flückiger et al, 2014; Kati et al, 2015). Moreover, resource realization proved to be a relevant factor for predicting treatment success in psychosomatic and alcohol-dependent patients one year after treatment (Deppe-Schmitz et al, 2009; Deubner-Böhme et al, 2011).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Psychotherapeutic research and interventions mostly focus on problematic aspects of functioning and the reduction of psychopathological symptoms (Kati, Stumpf, Heuft, Burgmer, & Schneider, ; Seligman & Csikszentmihalyi, ). This view on the dysfunctional aspects of individuals with mental disorders is one‐sided because persons with mental disorders not only suffer from psychopathological symptoms but also have strengths and abilities at the same time (Meister & Haug, ; von Wachter & Hendrischke, ).…”
mentioning
confidence: 99%
“…Another study found that alcohol‐dependent inpatients realized fewer resources compared to healthy control participants, but the study did not include a comparison with other diagnostic groups (Deppe‐Schmitz, Deubner‐Böhme, Lindenmeyer, & Schulz, ). Further studies showed that a person's level of resources is not a stable factor, and can be increased in psychotherapy (Deubner‐Böhme et al, ; Groß et al, ; Kati et al, ). Moreover, psychotherapy helped patients to permanently decrease the level of incongruence and to improve therapy success (Groß et al, ; Trösken & Grawe, ).…”
mentioning
confidence: 99%